Digital photogrammetry: comparison of digital orthophoto based on different dataset of digital images of aerial photograph - Ahmad, Anuar; Adnan, Nur Azhani (2008)
Data is an essential component in Geographic Information System (GIS), where it represents 70% of GIS. There are many techniques to acquire GIS data such as field work, photogrammetry, remote sensing, Global Positioning System (GPS) and source from existing data (primary data). Photogrammetry is one of the technique of data gathering and has become the earliest data source in topographic mapping. Photogrammetry has evolved from analogue to digital technique parallel with the development in digital camera technology. Orthophoto is one of the output of photogrammetry. Orthophoto can be produced from large format and small format aerial photo. This study is carried out to compare orthophoto between large and small format aerial photo. For large format aerial photo, two photographs are used. However, for small format aerial photo, about 20 photographs are used to cover the same area of the large format and the aerial triangulation procedure has to be carried out for the small format aerial photo. The processing of aerial photo processing was carried out using digital photogrammetry technique and ERDAS IMAGINE 8.6 software. The orthophoto were compared from the aspect of visualization, accuracy, time and cost to produce it. Results from this study showed that the orthophoto produced from large format aerial photograph (RMSE Â±0.676m) is much better than orthophoto produced from small format aerial photograph (RMSE Â±2.321m). In this study, it can also be concluded that the product from small format aerial photograph can be used for GIS application if the required accuracy is not so important and when large format aerial photography is not feasible to be executed.